Agrarian modernization in Gipuzkoa: Oñate and Yurreamendi (1851-1869) - Berriochoa Azcárate, Pedro (Huarte de San Juan. Geografía e Historia, 2018)
The first goal of this article is to demonstrate that Gipuzkoa, like the other Basque Provinces, has had an agrarian importance that has not been well covered by its historiography. In addition, the text seeks to highlight the relevance that the Basque provincial institutions gave to the agricultural sector. Faced with a certain inanity on the part of the State, the regional administrations appear to us as pioneers in the attempts to modernize the Basque agriculture. In this context we have to frame Oñate and Yurreamendi, two Elizabethan agrarian institutions. Oñate was a Practical School of Agriculture (1851-1869) that emerged after the Pidal Plan, which trained agricultural experts in an era of educational and pedagogical indefinition. Yurreamendi (1856-1867), a model house in Toulouse (Gipuzkoa), was a centre of agrarian experimentation promoted by the provincial institutions to improve the productivity of the farm. The conclusions of the work reinforce what was said in the objectives and aim to contribute a novel knowledge to the Basque and Spanish agrarian history. At the same time, they intend to underline the gradual modernizing changes that the Spanish agriculture faces throughout the nineteenth century.
Keywords: Gipuzkoa; sector agrario; institutions; modernization; agrarian sector